Burning Mouth Syndrome and Contact Dermatitis. Issue 4 (July 2020) - Powell, Alva; Nelson, Kamaria N.; Awosika, Olabola; Rengifo-Pardo, Monica; Ehrlich, Alison
Abstract : N/A: Burning mouth syndrome (BMS) is a condition that remains a diagnostic challenge and is frequently difficult to treat. Rather than being a singular entity, more recent research has suggested that the diagnosis of BMS encompasses a family of syndromes. Of this family, type 3 has been identified as being related to contact dermatitis. Although this subtype has been most commonly associated with dental allergens, several food, cosmetic, and pharmaceutical products have also been identified as allergens related to the onset of BMS. Failure to identify these allergens prevents timely diagnosis and initiation of treatment for patients with BMS related to contact dermatitis. This article identifies the allergens most relevant to this type 3 and describes the commercially available allergy panels needed to ensure that all relevant allergens are included during patch testing. This study also describes approaches to diagnosis of BMS and discusses approaches to treatment based on subtypes of the condition.